Piezo1 mutant zebrafish as a model of idiopathic scoliosis - Ramli,; Aramaki, Toshihiro; Watanabe, Masakatsu; Kondo, Shigeru (Frontiers in Genetics, 2024)
Scoliosis is a condition where the spine curves sideways, unique to humans due to their upright posture. However, the cause of this disease is not well understood because it's challenging to find a model for experimentation. This study aimed to create a model for human idiopathic scoliosis by manipulating the function of mechanosensitive channels called Piezo channels in zebrafish. Zebrafish were chosen because they experience similar biomechanical forces to humans, particularly in relation to the role of mechanical force in scoliosis progression. Here we describe piezo1 and piezo2a are involved in bone formation, with a double knockout resulting in congenital systemic malformations. However, an inframe mutation of piezo1 led to fully penetrant juvenile-onset scoliosis, bone asymmetry, reduced tissue mineral density, and abnormal intervertebral discs-resembling non-congenital scoliosis symptoms in humans. These findings suggest that functional Piezo channels responding to mechanical forces are crucial for bone formation and maintaining spine integrity, providing insights into skeletal disorders.